Aging hardening characteristic and electrical conductivity of Cu-Cr-Zr-Mo in situ composite - Wang Song; Zheng Tingting; Xie Ming; Chen Yongtai; Zhang Jiming (Science and Engineering of Composite Materials, 2016)
Cu-0.85Cr-0.5Zr-0.5Mo in situ composite was prepared by continuous casting, cold drawing, and aging treatment. By means of the analysis of microhardness, electrical conductivity, and transmission electron microscopy, the aging characteristics and microstructures of the in situ composite were investigated at different aging temperatures and aging times after cold deformation. The results show that the Cu-0.85Cr-0.5Zr-0.5Mo in situ composite has an excellent combination of the microhardness and electrical conductivity aged at 500°C for 4 h, and the microhardness and electrical conductivity reach 171 HV and 81.3% IACS, respectively. Small dispersed particles could strongly pin dislocations and stabilize the substructure from deformation. The main strengthening mechanisms for the in situ composite alloy are the work hardening and the secondary phase or interface strengthening. It was suggested that cold deformation before aging treatment can accelerate the precipitation of the secondary phase and improve the comprehensive properties of the Cu-Cr-Zr-Mo in situ composite.